Zhāhir dan Bāthin, Penafsiran Ibn ‘Arabi terhadap Ayat Ketuhanan - Win Usuluddin; Muhammad Faiz (UIN Kiai Haji Achmad Siddiq Jember, 2021)
The verses of the Qur'an are believed to contain several meanings, among which are the substances known as the meanings of zhāhir and bāthin. But in practice, in the interpretation of ahkam (fiqh), for example, it is more of His zahir meaning than His inner meaning. At the same time, the interpretation of Sufism has more inner meaning than zhāhir. In the theology that impacts the things that happened to Ibn Arabi, he is stated by some scholars because of his collaborative concept of divinity. However, many ulama'-ulama' also understand the true meaning of Ibn Arabi's teaching because it is considered a form of interpretation based on zhāhir and zāthin. Based on this, the focus of the problem of this research is, first, how is zhāhir and bāthin in Ibn Arabi's perspective, and second, how is zhāhir and bāthin in Ibn Arabi towards the divine verse. This research uses an approach with a descriptive-analytical method, and the type of research is library research. The results of this study are: first, zhāhir and bāthin Ibn Arabi's perspective is a duality concept that cannot be separated, especially in the realm of Sufism; second, Ibn Arabi in overseeing the divine verse, which is a representation of His Wahdat al-Wujūd, does not balance meaning and balance and the two run in harmony.